2002
DOI: 10.1098/rspa.2001.0866
|View full text |Cite
|
Sign up to set email alerts
|

Wavelet analysis of matrix–valued time–series

Abstract: The construction of matrix-valued filters for multi-resolution analysis of matrixvalued time-series is studied. Several different designs are explicitly derived corresponding to perfect reconstruction orthonormal filter banks. The resulting matrixvalued scaling functions and wavelet functions are calculated. Two of the derived filter classes have variable parameters providing rich classes of designs. A discrete matrix-valued wavelet transform and inverse transform is fully described and applied to a 2 × 2 time… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2004
2004
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 31 publications
(18 citation statements)
references
References 8 publications
(12 reference statements)
0
16
0
Order By: Relevance
“…For instance, in the application of feature recognition in EEG (electroenceph alography) data, it is necessary to model and analyze vector-valued signals which are also called multichannel signal with possibly intricate correlations among some of these channels [5]. In voice privacy systems a number of signals may need to be transmitted from one point to another, intermixing of the signals before transmission via matrix-valued filters, combine with perfect reconstruction, adds greatly to the likelihood of secure communications [10]. Fluid flows in oceanography and aerodynamics are usually represented as two-dimensional or three-dimensional vector fields in 2-D or 3-D space [11].…”
Section: Introductionmentioning
confidence: 99%
“…For instance, in the application of feature recognition in EEG (electroenceph alography) data, it is necessary to model and analyze vector-valued signals which are also called multichannel signal with possibly intricate correlations among some of these channels [5]. In voice privacy systems a number of signals may need to be transmitted from one point to another, intermixing of the signals before transmission via matrix-valued filters, combine with perfect reconstruction, adds greatly to the likelihood of secure communications [10]. Fluid flows in oceanography and aerodynamics are usually represented as two-dimensional or three-dimensional vector fields in 2-D or 3-D space [11].…”
Section: Introductionmentioning
confidence: 99%
“…Many interesting papers on this topic have been published (see Refs. 7,[9][10][11][12]14,19,[21][22][23], for technical books we refer the reader to Refs. 3 and 4.…”
Section: Introductionmentioning
confidence: 99%
“…[30]) concentrate on satisfying the conditions of Proposition 4. As a result, the ad-hoc form of the scaling filters limits the achievable properties.…”
Section: B Non-trivial Matrix-valued Scaling Filtersmentioning
confidence: 99%
“…If det Unlike [30], we will not include this technical su cient condition in the design. However, in this form it is simple to calculate and check for a given scaling filter, and we found that all constructions in this paper satisfy it.…”
Section: B Necessary Constraintsmentioning
confidence: 99%
See 1 more Smart Citation